تشبہ بالکفار : فقہی قواعدکا عصری انطباق (Al-Qamar, 2022)
Imitation of non-Muslims has ever been the important issue since the fall of Muslim civilization and rise of Western civilization. Islam being a complete code of life always offers complete guidance to its followers so is the case with this issue too. The Islamic Jurists derive legal guidance from the Quran and Sunnah in shape of rulings and designate it as Legal Maxims. These legal maxims cover all aspects of human life in general and at a larger scale. This study is focused about imitation of non-Muslims in daily life and its status according to legal maxims whether imitation of infidels is permissible or not. If not, then what is status of it, prohibited or undesirable. These legal maxims were described centuries ago, but these legal maxims cover the current era too. This study has been focused to examine these issues of imitation in the light of these legal maxims and endeavored to define solutions of these issues. This study will provide consciousness among Muslims and provoke willingness to follow the basic rulings of Quran and Sunnah.
Keywords: Legal Maxims; Imitation of Infidels; Muslims; West; Islam